+0  
 
+5
477
1
avatar+285 

Simplify (ab^2)(5a^2b^3)(3a^3)

 Dec 18, 2014

Best Answer 

 #1
avatar+20981 
+10

(a·b²)(5·a²·b³)(3·a³)  =  (5·3)(a·a²·a³)(b²·b³)  =  (15)(a6)(b5)  =  15a6b5

(add exponents when you multiply numbers with the same base)

 Dec 18, 2014
 #1
avatar+20981 
+10
Best Answer

(a·b²)(5·a²·b³)(3·a³)  =  (5·3)(a·a²·a³)(b²·b³)  =  (15)(a6)(b5)  =  15a6b5

(add exponents when you multiply numbers with the same base)

geno3141 Dec 18, 2014

36 Online Users

avatar
avatar
avatar
avatar